Outcome of resection of infratemporal fossa tumors. Issue 11 (16th January 2013) - Givi, Babak; Liu, Jeffrey; Bilsky, Mark; Mehrara, Babak; Disa, Joseph; Pusic, Andrea; Cordeiro, Peter; Shah, Jatin P.; Kraus, Dennis H.
<x xml:space="preserve">Abstract</x> Background A variety of tumors arise in or extend to the infratemporal fossa. We investigated the outcome of surgical management of these tumors. Methods We conducted a retrospective review of a craniofacial approach to resection of infratemporal fossa tumors from 1992 to 2008 in a cancer center. Results Forty‐three patients underwent resection of a infratemporal fossa tumors (68% men). Median age was 46 years (range, 1–81 years). The most common pathology was sarcoma (13; 30%). Twenty‐two tumors (51%) were recurrent. Twenty patients (46%) underwent resection of tumors from the infratemporal fossa, 5 (12%) required resection of the anterior skull base, and 18 (42%) required orbital exenteration, additionally. Thirty‐one patients (72%) required reconstruction with free tissue transfer. Twenty‐seven patients (62.8%) required further treatment with radiation and/or chemotherapy. Complications occurred in 9 patients (21%). Six patients (14%) underwent salvage operations. Median follow‐up was 24 months. Median overall survival and 3‐year survival were 40 months and 59.6%. Conclusion Tumors involving the infratemporal fossa can be resected with acceptable morbidity and long‐term survival. © 2013 Wiley Periodicals, Inc. Head Neck, 35: 1567–1572, 2013